Spatial heterogeneity of plant diversity-productivity-carbon nexus in eastern Loess Plateau grasslands - Haiyan Pang; Jia Mi; Yao Su; Jincheng Shi; Zonghao Zhou; Jing Shi; Shencong Hu; Xiang Zhao; Kuanhu Dong (PLoS ONE, 2026)
This study investigated a grassland ecosystem in the eastern part of the Loess Plateau. Based on the field investigation data from 70 typical grassland sample points in Shanxi Province, we systematically analyzed the regional differentiation characteristics. This analysis revealed the relationship between environmental factors and these key ecological indicators, and established a model for prediction. The results showed that: (1) plant diversity presented a significant altitude-differentiation pattern. The Margalef richness index increased significantly with increasing altitude, whereas the Pielou evenness index decreased significantly. This is closely related to the restricted water and heat conditions, weakened human interference, and changes in the competitive patterns of functional groups in high-altitude areas. (2) There were significant differences in the diversity, biomass, and soil properties among the different grassland types. Temperate shrub grasslands and mountain meadows had high plant diversity and soil carbon-nitrogen ratio. Their complex vegetation structures and refractory litter are conducive to soil carbon sequestration. (3) Soil organic carbon density (SOCd) and net primary productivity above ground (ANPP) show a spatially coordinated distribution pattern. The southern part of the Taihang Mountains and the southwestern section of the Luliang Mountains are high-value areas. The loess hilly area in the northwest of Shanxi Province is characterized as a low-value area due to soil erosion and drought. (4) The regression model constructed based on climatic factors and vegetation characteristics indicated that the average annual temperature and annual precipitation had a significant positive impact on soil carbon content, whereas soil pH and the relative biomass of gramineous plants had a negative effect on species richness. This study revealed the spatial heterogeneity of the structure and function of the grassland ecosystem in the eastern Loess Plateau and its environmental driving mechanisms, providing a scientific basis for regional grassland restoration, carbon management and biodiversity conservation.